Incidence and antibiotic susceptibility pattern of Escherichia coli and Staphylococcus aureus isolated from meat pie sold in a Nigerian North Central town - Obande, Godwin Attah; Umeh, Ebele U.; Azua, Emmanuel Terese; Chuku, Aleruchi; Adikwu, Peter (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Meat pie is a popular ready-to-eat food sold in Nigeria and is consumed by people of all classes and category. The study aimed to determine the incidence and susceptibility of Escherichia coli and Staphylococcus aureus isolated from meat pie to antibiotics commonly administered in Makurdi. Material and Methods: A total of 180 samples were collected and evaluated for bacterial contamination and presence of antibiotic-resistant Escherichia coli and Staphylococcus aureus. Contaminants were isolated and identified using biochemical test. Antimicrobial susceptibility of isolates was determined using the Kirby-Bauer disc diffusion method. Results: Eleven bacterial genera was identified. Bacillus spp (85%) occurred most frequently, followed by Staphylococcus aureus (38.9%), while Edwardsiella spp (2.8%) occured the least. Staphylococcus aureus was highly resistant to Cloxacillin (87.1%) but highly susceptible to Ofloxacin (88.6%). Escherichia coli was resistant to Amoxycillin, Tetracycline, Cloxacillin and Augmentin but susceptible to Gentamicin and Ofloxacin. Conclusion: Meat pie sold in Makurdi habours Staphylococcus aureus and Escherichia coli with multiple antibiotic resistance. Regulation of the production and retail process of meat pie is advocated as a possible means of reducing contamination and the risk of transferring antibiotic resistant bacteria to consumers.